Study of virulence factors of Aeromonas hydrophila isolates causing acute abdominal dropsy and ulcerative diseases in Indian major carps - Shome, Rajeshwari; Shome, B R; Ram, Nagesh (Indian Journal of Fisheries, 2011)
Six Aeromonas hydrophila isolates from acute abdominal dropsy andulcerative disease cases were evaluated for their virulence determinants.Morphological and biochemical characters' similarity index, ranged from 0.866-0.978 in relation to the first isolated A. hydrophila (3/95) when 46 parameterswere considered. Similarity index for virulence determinants varied from0.576-0.846 in similar comparisons taking proteolytic enzymes, amylase,cytotoxicity, dermonecrotic factor, haemagglutination and hemolysis intoconsideration. Generally, the haemagglutination of fish and chicken RBCappeared closely related to virulence in our isolates. Protease activity and theirthermostability in extracellular preparation in highly virulent and weaklyvirulent strains were not significantly different. However, presence of eitherthermostable or thermolabile or both types of metalloprotease and serineproteaseseem to be related to virulent strains, but none reflect the actual virulence.Mannose sensitive and resistant haemagglutination pattern indicates that acommon mechanism does not exist for agglutination of different species andhighly virulent isolates appear to possess different strategies for adherenceand colonization. Western blot analysis showed that all the isolates sharedatleast one common immunogen of 52 KD. However, its significance in relationto virulence has not been fully established.